2013
DOI: 10.2147/vhrm.s50831
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive overview: efficacy, tolerability, and cost-effectiveness of irbesartan

Abstract: BackgroundHypertension represents a major health problem, affecting more than one billion adults worldwide. Irbesartan, an angiotensin II receptor blocker, is considered to be a highly effective treatment in the management of hypertension. The purpose of this review is to evaluate the efficacy, safety and tolerability profile , and cost-effectiveness of treatment with irbesartan in hypertension.MethodsA review of the literature was conducted using the electronic PubMed and Cochrane Library databases and the He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 91 publications
(120 reference statements)
1
6
0
Order By: Relevance
“…However, this comes at an incremental cost that ranges between SAR 53.12 (USD 14.16) and SAR 144.96 (USD 38.66) per 1 mmHg reduction in SBP or DBP. These findings are consistent with the previously published studies which found that ACEIs/ARBs, such as lisinopril and irbesartan, were more cost-effective than amlodipine in the management of essential HTN [ 14 , 17 ]. These incremental benefits were more evident when ACEIs/ARBs, such as valsartan, were compared to amlodipine among patients with type 2 diabetes and microalbuminuria [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, this comes at an incremental cost that ranges between SAR 53.12 (USD 14.16) and SAR 144.96 (USD 38.66) per 1 mmHg reduction in SBP or DBP. These findings are consistent with the previously published studies which found that ACEIs/ARBs, such as lisinopril and irbesartan, were more cost-effective than amlodipine in the management of essential HTN [ 14 , 17 ]. These incremental benefits were more evident when ACEIs/ARBs, such as valsartan, were compared to amlodipine among patients with type 2 diabetes and microalbuminuria [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although several studies have compared the efficacy and cost effectiveness of different ACEIs/ARBs and amlodipine in the management of essential HTN, the findings of these studies should be carefully interpreted due to the substantial variability of the patient characteristics and the acquisition costs of antihypertensive drugs. Moreover, these studies were not conducted among Middle Eastern or Saudi patient populations [ 13 , 14 , 16 , 17 , 18 , 19 ]. Therefore, examining the impact of ACEIs/ARBs and amlodipine on SBP and DBP when used as a monotherapy among patients with essential HTN in Saudi Arabia would be very informative to health practitioners and policy makers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many pharmacoeconomic studies of antihypertensive medicines conducted in recent years have found control of hypertension to be cost effective. Several systematic reviews of these studies also have been published, but their focus has been on a specific medicine, such as irbesartan, 11 or medicine class, such as ACEIs or ARBs. 12 Thus, no comprehensive review has been conducted for studies across all anti-hypertensive medicine classes.…”
Section: Contextmentioning
confidence: 99%
“…Unlike other studies, AIMS assessed the effects of irbesartan in Marfan syndrome. Irbesartan is a selective angiotensin type-1 receptor blocker with greater bioavailability and a longer half-life than losartan (11–15 h for irbesartan vs 6–9 h for losartan), with more powerful antihypertensive effects 25, 26. Irbesartan might also have effects on the pathophysiology of aortic disease, including TGF-β pathways 7 .…”
Section: Discussionmentioning
confidence: 99%